SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL EVALUATION OF N-(4-MORPHOLIN-3-FLUOROPHENYL)-N-(FURAN-2-YLMETHYL)-2- SUPSTITUTED PHENOXYPROPANAMIDE DERIVATIVES - LOGANATHAN VELUPILLAI; M.S. SHINGARE; D.V.MANE (International Journal of Pharma and Bio Sciences, 2015)
A novel series of eight novels N-(4-Morpholin-3-fluorophenyl)-N-(furan-2-ylmethyl)-2-substituted phenoxypropanamide derivatives (8 E – 8 L) have been synthesized from commercially available 3,4-Difluoronirobenzene as a starting material. High yield and high purity indicates lack of side reaction and by product. The chemical structures of the synthesized compounds were confirmed by means of 1HNMR and mass spectral data. The synthesized compounds were then examined for their antibacterial and antifungal activities. Some of them were found to possess good activity.